Static and dynamic changes of natural head position improve vertical eye canting of patients with non-syndromic asymmetric facial deformities after orthognathic surgery - Sun, Wei; Zhao, Tianyu; Tang, Yuxin; Li, Xiang; Gao, Siyong; Zheng, Guangsen (Frontiers in Surgery, 2026)
ObjectiveBy combining static and dynamic methods of obtaining natural head position, this study examined whether compensatory head tilt in patients with non-syndromic asymmetric facial deformities contributes to of pseudo-“vertical eye canting”.MethodologyPatients with non-syndromic asymmetric facial deformities patients and symmetric dento-maxillofacial deformity who met the inclusion and exclusion criteria were divided into observation and control groups. Static photographs were measured to analyze the static head position of the subjects in each follow-up period; dynamic natural head positions of the subjects in different states in each period were recorded by posture sensors for dynamic analysis. Intergroup and intragroup changes were analyzed with Mann–Whitney U-test and one way ANOVA.ResultsThe static natural head position of the observation group at 1 year after surgery was significantly different from that of the pre-surgery period, whereas each dynamic natural head position at all follow-up periods after surgery was significantly different from dynamic natural head position of the pre-surgery period. The range of dynamic head position in the rolling direction was smaller in the observation group than in the preoperative period at 6 months and 1 year after surgery, but the dynamic head position range in the rolling direction was not significantly different in the control group at the different follow-up stages.ConclusionsChanges in natural head position (NHP) following orthognathic surgery were associated with improved stabilization of head posture in roll orientation and reduced pseudo-eye canting in non-syndromic asymmetric facial deformities (NSAFD) patients. Clinical Trial Number KQEC-2021-58-01.